If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -8) = 18 Reorder the terms: -3(-8 + x) = 18 (-8 * -3 + x * -3) = 18 (24 + -3x) = 18 Solving 24 + -3x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -3x = 18 + -24 Combine like terms: 24 + -24 = 0 0 + -3x = 18 + -24 -3x = 18 + -24 Combine like terms: 18 + -24 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| (6x+20)+(2x+4)=164 | | (3x+2)/4=16-2x | | Y+3/r=r^2 | | 3,823=5/100 | | -2(7y-5)=-14y-23 | | -18-11r=2b | | 1/4+1/5+1/2+150 | | 2(3z+1)-8=48 | | 8-5(z+2)=-2(5z-2)-2 | | 2x+11+x+7=18 | | n+3.1n-4.7=3.6(n-4.5) | | 0.168x=0.2x+0.667 | | 3(x+3)-6x=2(4-2x) | | -145=7r+2(7r+1) | | 6(x-5)=4(2x-1) | | 3x+9=44-2y | | M*0= | | -2.7u+5.3=-1.4u-2.5 | | 2/3/87 | | 3w-(6+w)=12 | | 17=2k+8+k | | 90(2/5) | | 6(x+3)=3(8+4x)-6x | | V/-50=30 | | 2x+4/3x=290 | | -5(-3x-3)=60 | | -4k-4(8k-1)=148 | | 2/3x+1/4x=x-3.75 | | .33+2z=-5/6 | | 2n+10=5n-5 | | 90(-2/5) | | -2(x-3)+3x=12 |